Perilaku Asertif dan Kecenderungan Kenakalan Remaja Berdasarkan Pola Asuh dan Peran Media Massa - Sriyanto, Sriyanto; Abdulkarim, Aim; Zainul, Asmawi; Maryani, Enok (Faculty of Psychology, Universitas Gadjah Mada, 2014)
Theoretically the adolescent psychological development is a transition period which is marked by changes in biological, psychological and social aspects. Empirically, the increasing trend of juvenile delinquency is caused by the inability of the early adolescents to be assertive so that their personality become weak and they can easily fall into negative things. This study aimed at determining the extent to which environment and mass media have the influence on assertive behaviour and juvenile delinquency trend in Junior High School in West Java Province. The respondents of this research were 458 students of Junior High Schools in West Java. Questionnaire was used to collect the data. Samples were chosen by using stratified random sampling technique. Data analysis employed Structural Equation Modelling (SEM) with two-stages testing: measurement model and structural model, using Analysis of Moment Structure (AMOS). The results of this study revealed that all hypothetical statements have significant effects. The findings showed that the increasing level of students’ assertive behaviour can decrease the tendency of juvenile delinquency in them. Keywords: assertive behaviour, parenting, mass media, juvenile delinquency trend